SIRT1 is Required for Exercise-Induced Beneficial Effects on Myocardial Ischemia/Reperfusion Injury - Wang D; Cao H; Wang X; Wang J; Wang M; Zhang J; Wang L (Dove Medical Press, 2021)
Dawei Wang,1,* Hongyan Cao,2,* Xu Wang,3 Jinchun Wang,4 Manli Wang,5 Jian Zhang,6 Lin Wang6 1Department of Emergency, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of China; 2Department of Cardiology, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of China; 3Department of Colorectal and Anal Surgery, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of China; 4Department of Emergency, Jilin Provincial FAW General Hospital, Changchun, 130011, People’s Republic of China; 5Department of Geriatrics, Changchun Central Hospital, Changchun, 130000, People’s Republic of China; 6Department of Cardiovascular Center, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Zhang; Lin WangDepartment of Cardiovascular Center, The First Hospital of Jilin University, No. 71, Xinmin Street, Changchun, 130021, Jilin Province, People’s Republic of ChinaTel +86-0431-88783417Email wanglinjdyy@jlu.edu.cn; Kenny1026@jlu.edu.cnBackground: Exercise training has been regarded as an effective mean of prevention and treatment of cardiovascular diseases (CVD), and exercise can improve the antioxidant capacity of the myocardial. While SIRT1 has been proved to protects the heart from myocardial ischemia/reperfusion (MI/R) injury and apoptosis, less is known about the association between exercise-induced cardioprotection and SIRT1.Methods and Results: MI/R injury model was constructed after swimming training in mice. Significantly reduced myocardial infarct size, decreased apoptosis ratio and upregulated SIRT1 protein expression in heart were found in swam mice by 2,3,5-triphenyltetrazolium chloride (TTC) staining of heart sections, TUNEL staining of frozen sections and Western blotting. The results of TUNEL staining and Western blotting suggested activation of SIRT1 using resveratrol (RSV) or inhibition of SIRT1 using EX527 in vitro blocked or accelerated cardiomyocytes apoptosis which induced by hypoxia/reoxygenation (H/R) respectively and regulated the expression of antioxidants in vitro. PGC-1α has been identified as one of the downstream genes of SIRT1 modulating oxidative stress and apoptosis. Importantly, the data of TTC staining, TUNEL staining, Western blotting, echocardiography and histopathological staining revealed that mice with inducible cardiac SIRT1-knockout blocked the protective effects of exercise preconditioning on myocardial infarct size, myocardial apoptosis, adverse ventricular remodeling, cardiac fibrosis and cardiac dysfunction after MI/R injury, simultaneously exercise-induced expression of myocardial antioxidant stress factors was hindered which was detected by immunohistochemical analysis.Conclusion: SIRT1 protects against oxidative stress after MI/R injury by activating downstream PGC-1α and promoting the production of antioxidant enzymes. SIRT1 is required for exercise to protect against myocardial apoptosis and maladaptive ventricular remodelling induced by myocardial ischemia/reperfusion injury.Keywords: exercise, myocardial ischemia/reperfusion injury, oxidative stress, SIRT1